The Role of Taxpayer Compliance in Mediating the Influence of Marketing Communication on Taxpayers’ Decisions at the Lubuk Pakam Primary Tax Office - Oktavino S Tampubolon, Boy; Muharram Ritonga, Husni; B, Mesra (International Conference Epicentrum of Economic Global Framework, 2025)
This study aims to analyze the effect of marketing communication on taxpayer decisions, with taxpayer commitment as an intervening variable, at the Lubuk Pakam Primary Tax Office. This study uses a quantitative approach with a survey method. The research sample consisted of 293 respondents obtained through probability sampling using the Slovin formula. Data were collected using a questionnaire with a Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. The results indicate that marketing communication has a positive and significant effect on taxpayer decisions. Marketing communication also has a positive and significant effect on taxpayer commitment. Furthermore, taxpayer commitment has a positive and significant effect on taxpayer decisions. The results of the indirect effect test indicate that taxpayer commitment significantly mediates the effect of marketing communication on taxpayer decisions. The coefficient of determination indicates that marketing communication explains 15.8 percent of taxpayer commitment, while taxpayer compliance decisions are explained by marketing communication and taxpayer commitment by 48.8 percent. These findings suggest that improving the quality of marketing communication can strengthen taxpayer commitment, which ultimately promotes increased tax compliance at the Lubuk Pakam Primary Tax Office.